The relationship between psychological capital and work engagement of kindergarten teachers: A latent profile analysis - Gao, You; Yue, Yaping; Li, Xiaomin (Frontiers in Psychology, 2023)
This study adopts a person-centered approach to explore kindergarten teachers’ psychological capital and its relationship with work engagement through latent proﬁle analysis (LPA). In this study, 2,790 kindergarten teachers in Shaanxi Province, China were recruited and assessed by the Chinese Indigenous Psychological Capital Scale and the Utrecht Work Engagement Scale. The results showed that: (1) the psychological capital of kindergarten teachers was divided into three latent proﬁles: “rich type” (43.2% of the sample), “medium type” (46.3%), and “poor type” (10.5%); (2) there were significant differences in the location of the kindergarten, the type of kindergarten, and the teaching experience among the three latent profiles of psychological capital. The proportion of “rich type” kindergarten teachers was all lowest among rural, private, and less than five years teaching experience kindergarten teachers, while “middle type” and “poor type” teachers accounted for the majority;(3) the latent profiles of psychological capital were significant influencing factors of work engagement, and the order of mean scores of total work engagement and its three sub-dimensions from high to low was“rich type” > “medium type” > “poor type” (all p<0.001); (4) After controlled the influence of the type of kindergarten, the location of kindergarten, and the teaching experience of teachers on kindergarten teachers’ work engagement, the psychological capital of kindergarten teachers was still an important factor which affected teachers’ work engagement.